Ljiljana Šarić Spatial Concepts in Slavic. A Cognitive Linguistics Study of Prepositions and Cases. Wiesbaden: Harrassowitz Verlag (2008) - Stanojević, Mateusz-Milan (2009)
Prikaz knjige Ljiljane Šarić Spatial Concepts in Slavic. A Cognitive Linguistics Study of Prepositions and Cases. Wiesbaden: Harrassowitz Verlag (2008)
Projekt MZOS
HRV